Robust integral sliding mode control for uncertain switched systems under arbitrary switching rules. (August 2020) - Zhang, Xiaoyu
Abstract: This article proposes a design of robust integral sliding mode control under arbitrary time-dependent switching rules for uncertain switched systems (SSs). First, a description of the control problem for the switched system is presented, after which a recursive searching method of the common Lyapunov function (CLF) for the robust stable matrix set is proposed. Based on the proposed CLF searching method, a common robust integral-type sliding mode surface is then designed, which is robust to the unmatched uncertainties. Consequently, a sliding mode controller is designed so that the system state remains on the sliding mode surface from the initial time instant. Finally, the correctness and performance of the proposed control design are verified through simulations. The controlled switched system with unmatched uncertainty in the sliding mode is robust stable under any time-dependent switching signal.